"Water-Carbon" redistribution caused by China's interprovincial grain transportation. (15th May 2023) - Sun, Jingxin; Sun, Shikun; Yin, Yali; Wang, Yubao; Zhao, Jinfeng; Tang, Yihe; Wu, Pute
Highlights: Grain water-carbon footprint was accounting in mainland China. Grain virtual water-carbon flow among regions was evaluated in mainland China. Water saving and carbon emission reduction based on grain transfer were evaluated. Challenges and opportunities in water-saving and carbon emission reduction were discussed. Abstract: Water resource and carbon emission involved in grain production in mainland China are redistributed among provinces as the grain was transported in recent years. This study first calculated the water consumption and carbon emission during the growth of grain crops based on the water-carbon footprint theory, and then used the social-equity method to calculate the inter-regional grain virtual water and virtual carbon flow. Finally, the regional and national trends in water saving and carbon emission reduction were calculated based on the spatial and temporal differences in grain planting among provinces. In terms of virtual water-carbon, from 2000 to 2017, the amount of the inter-provincial grain virtual water flow increased from 717.4 × 10 8 m 3 to 1472.6 × 10 8 m 3 . Heilongjiang and Guangdong are the provinces with the largest amount of grain virtual water outflow (670.9 × 10 8 m 3 ) and inflow (402.8 × 10 8 m 3 ) in 2017, respectively. And the total inter-provincial grain virtual carbon flow increased from 2362.7 × 10 4 t CO2 e to 12, 680.6 × 10 4 t CO2 e. Grain transport leads to water saving and carbon emission reduction, the amount of water saving increased from 25.6 × 10 8 m 3 to 77.0 × 10 8 m 3 and the carbon emission reduction increased from 2.4 × 10 4 t CO2 e to 847.4 × 10 4 t CO2 e from 2000 to 2017. Based on research results and from the perspective of socio-hydrology combined with water saving and carbon emission reduction, the regions could optimize the integration of water saving, carbon emission reduction, and sustainable development based on coordinating the grain planting structure according to their own climatic condition, soil and water resource condition, and socioeconomic condition. Graphical abstract: Image, graphical abstract